Pengaruh Resiko Kerja, Upah Dan Pengalaman Kerja Terhadap Produktifitas Kerja Pada PT. Sinar Niaga Sejahtera - Achmad Nizar Zulmy; Zaenul Muttaqien; Heru Sutapa (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to determine the influence of work risk variables (X1), wages (X2) and work experience (X3) on work productivity (Y). The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= 0.908 + 0.331X1 + 0.474X2+ 0.337 t test results: The wage variable has a partially significant effect on work productivity with a sig result of 0.002 <0.05. t test results: The work experience variable has a partially significant effect on work productivity with a sig result of 0.002 <0.05. The results of the F test obtained an Fcount of 116,338 with a significance value of 0.000 < 0.05.